Rituximab-Lenalidomide-Ibrutinib Combination for Relapsed/Refractory Primary CNS Lymphoma: A Case Series of the LOC Network. (28th September 2021) - Houillier, Caroline; Chabrot, Cecile Moluçon; Moles-Moreau, Marie-Pierre; Willems, Lise; Ahle, Guido; Waultier-Rascalou, Agathe; Fornecker, Luc-Matthieu; Hoang-Xuan, Khê; Soussain, Carole
Abstract : Background and Objectives: To evaluate the efficacy and tolerance of the association rituximab-lenalidomide-ibrutinib (R 2 I) in relapsed/refractory (R/R) primary CNS lymphoma (PCNSL). Methods: R/R PCNSL patients treated with R 2 I were retrospectively selected and analyzed from the French LOC database. Results: Fourteen patients (median age: 63 years, median Karnofsky Performance Status: 75%) received R 2 I, administered after a median of 2 previous lines of chemotherapy, including autologous stem cell transplantation (ASCT) in 5 cases. The best response was complete response in 4/14 patients and partial response in 4/14 patients, achieved in a median of 2.5 months. Three responder patients received consolidation treatment (WBRT: N = 2, ASCT: N = 1) after R 2 I, and R 2 I served as a bridge before CAR-T cell therapy for one patient. R 2 I was discontinued due to toxicity in 3/14 patients. There were no toxicity-related deaths. Discussion: The R 2 I combination resulted in a high rate of response of rapid-onset in heavily pretreated patients with poor prognosis, with manageable toxicity, and allowed 3 patients to proceed to consolidation. Although preliminary, these results support the use of R 2 I for R/R PCNSL failing conventional chemotherapies. Classification of Evidence: This study provides Class IV evidence that combination of rituximab-lenalidomide-ibrutinib induces a high rate of response in heavily pretreated R/R PCNSL.